Efficacy of Sertraline with Aripiprazole versus Paroxetine with Aripiprazole in Patient with Major Depressive Disorder - Adeel Memon, Muhammad Raza Memon, Ghulam Shabir Shaikh, Zuhaib Ahmed, Daim Meghwar, Fareea Mahmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Major Depressive Disorder (MDD) is the most severe form of depression and can be extremely debilitating for those afflicted. Treatment for MDD typically involves the use of antidepressant medications such as selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs). However, many patients do not respond adequately to these medications, leading to the use of adjunctive treatments, such as atypical antipsychotics. The combination of SSRIs and atypical antipsychotics has been found to be more effective than monotherapy with either medication alone. Aims: The Aim of this study is to compare the efficacy of two different combinations of antidepressants and atypical antipsychotics in the treatment of MDD: sertraline with aripiprazole, and paroxetine with aripiprazole. Study design and setting: Open-label trail. This study was conducted at Sir Cowasjee Jahangir Institute of Psychiatry & Behavioral Sciences, Hyderabad, Pakistan from October 2021 to October 2022. Materials and Methods: In this research trial, a total of 48 patients were randomized to receive either sertraline (100 mg/day) plus aripiprazole (5 mg/day) or paroxetine (20 mg/day) plus aripiprazole (5 mg/day) for a period of 6 weeks. The outcome measure was assessed by the change in Hamilton Depression Rating Scale (HDRS) score from baseline to 6 weeks. Data was analyzed statistically using SPSS version 26. Results: The overall mean age of patients with MDD was 36.52 ± 9.9 years; 56% female and 46% male were reported with MDD. There was a significant reduction in HDRS scores among both groups of drugs; however, no difference was found in terms of efficacy between the two groups. Conclusion: The combination therapy of aripiprazole augmentation, with the addition of either sertraline or paroxetine, was equally effective in patients with Major Depressive Disorder. Keywords: Major depressive disorder, MDD, Sertraline, Paroxetine, Aripiprazole, Augmentation therapy.